Testing for the rationality of central bank interest rate forecasts - Michael Frenkel; Jin-Kyu Jung; Jan-Christoph Rülke (Empirical Economics, 2021)
In this paper, we study the bias in interest rate projections of five central banks, namely the central banks of the Czech Republic, New Zealand, Norway, Sweden, and the USA. We examine whether central bank projections are based on an asymmetric loss function and report evidence that central banks perceive an overprojection of their longer-term interest rate forecasts as twice as costly as an underprojection of the same size. We find that forecast rationality is consistent with biased interest rate projections under the assumption of an asymmetric loss function, which contributes to explaining the behavior of the examined central banks and their forecasts.
Keywords: E43; E47; E58; 330; Asymmetric loss; Forecast rationality; Interest rate forecasts